The potential protective value of ants in Northern Australian coffee plantations. Issue 3 (2nd July 2020) - Bizumungu, Gabriel; Majer, Jonathan D.; Fay, Harry A. C.
Abstract: Native ants are the oldest example of biological control agents used in tropical tree crops. Unfortunately, intensification of agricultural practices has led to a simplification of habitat and subsequent loss of native ant biodiversity. This article describes research that evaluated the native and introduced ants present in the canopies of two Australian sun coffee plantations, their distribution pattern and their potential to limit pests. The presence in coffee plantations of a range of beneficial insects and parasites, plus the effect of ants, most notably Iridomyrmex suchieri Forel, may maintain potential pests at low levels in coffee plantations. These effects may be important for future biological control programs of coffee pests in Australia, although the sun coffee grown here does not harbor a large variety of canopy ant species.